Effect of a new teat dip on somatic cell count, incidence of Mastitis, and milk production in a commercial dairy - John E. Shirley; W.F. Miller; J. Rottinghaus; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2004)
Five hundred and thirty Holstein cows located in a commercial dairy herd near Birdseye, Indiana, were used to evaluate an iodophor (0.50% iodine) teat dip containing a new conditioner. The new teat dip (Dinerin) was evaluated against a common commercial teat dip (WestAgro Iodozyne pre-dip and West- Agro Blockade post dip). The study was conducted February 17 through June 25, 2004. Cows treated with Dinerin teat dip had lower somatic cell counts and produced more milk than those treated with the WestAgro products.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Teat dip; SCC; Milk yield